72 numaralı mühimme defteri ( h.1002-1003 ) (vr. 231-473) inceleme-metin - Şahin, Zafer (My University, 2014)
Divân-ı Hümâyûn Osmanlı Devleti merkez teşkilatının en mühim müessesesi idi ve devletin siyasî, askerî, malî isleriyle meşgul olur, her türlü dava ve şikâyetlere bakardı. Divân-ı Hümâyûn'da alınan kararlar, ferman, berat ve hükümlerin nakil kısmı Divân-ı Hümâyûn sicilleri olarak da bilinen mühimme defterlerine kaydedilirdi. Özellikle padişaha ait belgelerden birisi olan ferman sefer açılması, asker sevki, vergi, vs. devlet islerine dair, doğrudan doğruya Divân-ı Hümâyûn'un kararı ve padişahın emri üzerine hazırlanıp ilgili şahıslara gönderilirdi. Konumuz olan mühimme defterleri Divân-ı Hümâyûn kalemlerinden Beylikçi veya Divân Kalemi diye adlandırılan kalem dairesinde mühimmenüvisân denilen kâtipler tarafından kaleme alınır ve hıfzedilirdi. Kaleme alınan bu mühimme defterlerindeki hükümlerin üstlerinde, hükümlerin nasıl meydana geldiği, ne gibi muamele gördüğü veya cevabın mahiyeti ile ilgili olan ve zamanla, belki de Reisü'l-küttab'ın yönlendirmesine göre değişiklik gösteren çeşitli kayıtlar mevcuttur. Bu kayıtlar Osmanlı bürokrasisi bakımından olduğu kadar diplomatiği açısından da ehemmiyet arz etmektedir. Transkripsiyon ve değerlendirmesini yaptığımız 72 numaralı Mühimme Defteri, III. Murad (1594–1595) dönemine ait olup, H.(1003)/ M.(1595) yılını ihtiva etmektedir. Bu defterin ağırlıklı konusunu Avusturya seferleri, sefer hazırlığı, zahire temini, kale ve köprü yapımı ve tamiri oluşturmaktadır. Ayrıca incelediğimiz defterin şekil ve özellikleri, transkripsiyon ve değerlendirilmesi de bulunmaktadır. Çalışmanın sonuna indeks ilave edilmiştir. mme, sefer hazırlığı, zahire temini, kale ve köprü yapımı ve tamiri

Divân-ı Hümâyûn which is the most important body of the central organization of Ottoman Empire, was involved in political, military and financial affairs of the state. And take care of any actions and complaints therewith. The decrees resolved with The Royal state council Divân-ı Hümâyûn, the royal orders ferman, royal warrant and provisions were recorded with the ledger books called mühimme which was also known as the registration of The Royal state council Divân-ı Hümâyûn. Particulary the royal orders ferman, which was one of the exclusive documents of the sultans, used to be issued based on the direct resolutions of The Royal state council Divân-ı Hümâyûn, or otherwise the sultan's himself. For the matters particularly related to the major state affairs such as; declaration of wars, mobilization, taxes ete, and relayed to the authorities concerned accordingly. The ledger books, which constitute the subject matters of this study, were used to be written and kept by the royal clerks called mühimmenüvisân who as a matter of fact were employed in the royal clerk's Office Beylikçi (chancery office) or Divân Kalemi (the office of Secretary of State Council). Over the provisions included in these ledger books called mühimme are various notes showing many changes either related to the time, or the answer backs and how it was treated by the office and the process of the provision itself, probably including the direction of the Reisü'l-küttab (Minister of foreign Affairs). Such notes and records are important in terms of Ottoman Bureaucracy and diplomacy. The Number 72 Muhimme Book, whose transcription and evaluation we carry out in this study, belongs to the reign of Murad III (1594-1595) and includes the decisions made in 1595 (in 1003 of Hegira Calendar). This book is mainly the subject of the Austrian expedition, expedition preparation, grain supply, constitute the castle and bridge construction and repair. In addition, form and characteristics of the book studied, transcription and evaluation of it are also included. An index was added at the end of the study. mme, preparation time, the grain supply, the castle and bridge construction and repair.
Keywords: Tarih